Diurnal and Seasonal variations of Heat-flow Into soil at Waltair - PADMANABHAMURTY , B. P.; SUBRAHMANYAM, V. P. (MAUSAM, 1961)
Heat-flow into the soil is evaluated indirectly from temperature profiles and measured directly transducer on representative days in different months. On calm and clear days, the heat conveyed in either direction (on a daily basis) is roughly of the same magnitude, but during transition months or when there are raped upward or downward trends of temperature variation, some positive or negative carry-over to the next day is observed. Significant features of the seasonal curves are the post-monsoon peak in the downward fluxes and early summer peak in the outward fluxes. The early evening minimum in the diurnal curves has the lowest magnitude in July and has another lower value between December and January and its highest value in March. The time of occurrence in course of day of this minimum is earlier in winter than in summer with a swing-back to its winter value immediately after the withdrawal of the southwest monsoon.